Does home-based work lead to women's empowerment? : a case study of Mahadevpur, Bangladesh - Naznin, Tahmina; Resurreccion, Bernadette P.; Doney, Philippe; Routray, Jayant Kumar; The Government of Japan (Pathum Thani, Thailand : Asian Institute of Technology, 2010)
In Bangladesh, women constitute half of the total population, but women{u2019}s socio-economic position particularly in the rural areas remains low. Women in the rural areas belong to the most deprived section of the society and many of them facing adverse conditions in terms of social subjection and economic disparity. Considering this circumstances, this study investigates the extent of rural home ba sed women worker{u2019}s empowerment and factor influencing it. The study was conducted among three types of home-based women worker; embroidery, pottery and net weavers in Manikgonj district, Bangladesh. The success of Home-based activities is often evaluated solely in terms of economic outcomes. These evaluations do not recognize how opportunities may differ across groups and contexts. The distribution of empowerment indicators show that due to an individual source of income embroidery group owned more assets compared two others group but they have limited control over it. It is now evident that the financial benefit gained from home-based work is not only for women but are also passed through children and men as. Participation in embroidery work is positively associated with a women{u2019}s level of empowerment as a function of her relative physical mobility, economic security, ability to make various purchases her own, freedom from domination and violence within the family. At the same time they are over burden by both productive and reproductive work, limited participation in political activities and community activities. The result through empowerment indicators varied according to the types of home-based work and not all groups are equally empowered by economic, social and gender perspective. It is clear that empowering changes may not be manifest to all dimensions even empowering effects may not be of similar magnitude. This suggested that the process of empowerment is more readily influenced at some dimension than at others.
A thesis submitted in partial fulfillment of the requirements for the degree of Master of Science in Gender and Development Studies, School of Environment, Resources and Development
Thesis (M.Sc.) - Asian Institute of Technology, 2010
Keywords: Home labor -- Bangladesh -- Mahadevpur; Women employees -- Bangladesh -- Mahadevpur